2015
DOI: 10.5271/sjweh.3529
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of qualitative literature on occupational health and safety legislation and regulatory enforcement planning and implementation

Abstract: This is the first systematic review of qualitative literature addressing political, economic and social processes and relationships that shape occupational health and safety (OHS) regulation. The meta-ethnography identifies calls for attention to challenges and opportunities for OHS regulation relating to non-standard work situations, grey zones of enforcement, politics of policy formation, and variation among employers and workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 39 publications
1
62
0
1
Order By: Relevance
“…Our study has limitations that should be noted. Although it was aimed at understanding how law and regulatory regimes can improve occupational health and safety of workers [ 80 , 81 ], the stakeholder engagement component was limited and did not include health worker associations. It is also possible that the mix of stakeholders who took part in the meetings resulted in a narrower range of expressed opinion than would have been the case had these groups met separately.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has limitations that should be noted. Although it was aimed at understanding how law and regulatory regimes can improve occupational health and safety of workers [ 80 , 81 ], the stakeholder engagement component was limited and did not include health worker associations. It is also possible that the mix of stakeholders who took part in the meetings resulted in a narrower range of expressed opinion than would have been the case had these groups met separately.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few cantonal inspectorates successfully employ participatory inspection techniques; exploring how this could be propagated in the context of Switzerland's liberal labour market seems a useful avenue of reflection. This could be interesting for other countries as well, since several studies have reported on a lack of contact between inspectors and workers (MacEachen et al, 2016;Stadler and Splittgerber, 2014).…”
Section: Interpretation Of the Findingsmentioning
confidence: 95%
“…A systematic review of this type of publication could be useful for government agencies confronted with the difficulty of tackling these issues. Previous systematic reviews have measured the impact of labour inspections in terms of injuries and occupational diseases (MacEachen et al, 2016;Mischke et al, 2013), but to our knowledge, there has not been any systematic review on labour inspector intervention for the prevention of psychosocial risks. Many countries have launched intervention programmes over the past 20 years.…”
Section: Introductionmentioning
confidence: 99%